A very short, fairly interesting and reasonably cheap book about management - Cunliffe, Ann L. (Los Angeles, California SAGE Publication Inc., 2021)
Ann Cunliffe breathes fresh air into topics that are central to management, organizational behaviour or leadership courses including what managers do, motivation, communication, and ethics and emphasises the importance of relations when thinking about management and drawing on a range of disciplines such as philosophy and linguistics.
Includes bibliographical references (pages 156-176) and index.
Keywords: Industrial management; Management